DESIGN OF A 2X2 ARRANGEMENT OF SLOT ANTENNAS IN RGW TECHNOLOGY FOR THE 60 GHZ BAND - Morales Roche, Taimir Alain; Arias Fernández, Deivis Richard; Marante Rizo, Francisco R. (Telemática, 2021)
This work proposes the design of an antenna for the 60 GHz band, using Gap Waveguide technology. For this, the fundamental aspects of antenna theory are first analyzed. In addition, the propagation in millimeter wave band is briefly characterized and the generalities of Gap Waveguide technology, its variants and state of the art are exposed. With these theoretical bases, an array of 2x2 slot antenna antennas is designed and simulated in the CST software, using the RGW variant. The simple element of the arrangement consists of an RGW structure with T-termination and a groove in the upper metal plate. A maximum gain of 12.4dBi and a bandwidth of 8 GHz is obtained, covering the entire desired band.